2019
DOI: 10.2147/jaa.s223093
|View full text |Cite
|
Sign up to set email alerts
|

<p>Once-daily fluticasone furoate/vilanterol combination versus twice-daily budesonide/formoterol combination in the treatment of controlled stable asthma: a randomized crossover trial</p>

Abstract: IntroductionFluticasone furoate (FF)/vilanterol (VI) dry powder inhaler (DPI) is the only once-daily maintenance inhaled corticosteroid (ICS)/long-acting β2 adrenergic agonist (LABA) combination for asthma. We aimed to compare the clinical effects of once-daily FF/VI and twice-daily budesonide (BUD)/formoterol (FM) DPI in patients with controlled stable asthma.MethodsWe performed a randomized crossover trial in which stable asthmatic patients controlled on ICS/LABA received 8 weeks of FF/VI (100/25 μg 1 puff o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The once-a-day combination of ICSLABA is also available that has an adherence advantage over twice-a-day combination. [ 70 71 72 73 74 75 76 ] Uncontrolled patients at step 4 may require additional therapy such as LAMA. Biologics are considered for uncontrolled patients with moderate-to-severe asthma based on phenotype.…”
Section: Impact Of Short-acting β-Agonists Overreliance On Asthma Gui...mentioning
confidence: 99%
“…The once-a-day combination of ICSLABA is also available that has an adherence advantage over twice-a-day combination. [ 70 71 72 73 74 75 76 ] Uncontrolled patients at step 4 may require additional therapy such as LAMA. Biologics are considered for uncontrolled patients with moderate-to-severe asthma based on phenotype.…”
Section: Impact Of Short-acting β-Agonists Overreliance On Asthma Gui...mentioning
confidence: 99%
“…First, many preparations of inhaled therapy for chronic airways diseases require twice-daily dosing and higher-frequency dosing is associated with reduced adherence ( 10 ). A small study from 2019 comparing the effectiveness of a once-daily preparation of preventer medication to a standard twice-daily regimen noted a statistically significant reduction in forgetfulness and inconvenience as measured by a questionnaire ( 11 ). Second, asthma symptoms are known to vary with the time of day, the season, and even where the person lives and works, as seen in occupational and allergic asthma.…”
Section: Causes Of Poor Adherence To Inhaled Treatmentmentioning
confidence: 99%
“…FF/Vi DPI is the first once-daily ICS/uLABA recently commercialized in India for the treatment of COPD (FF/Vi: 100/25 µg) and Asthma (FF/Vi: 100/25 µg and 200/25 µg) [ 10 ]. Landmark studies for FF/Vi in COPD and Asthma found improved symptom control, improved adherence, and a lower need for rescue medication with FF/Vi than with conventional ICS/LABA, including budesonide/formoterol (BUD/FOR) [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%